Episodic Binge-like Ethanol Reduces Skeletal Muscle Strength Associated with Atrophy, Fibrosis, and Inflammation in Young Rats - Caceres-Ayala, Constanza; Mira, Rodrigo G.; Acuna, Maria Jose; Brandan, Enrique; Cerpa, Waldo; Rebolledo, Daniela L. (My University, 2023)
Binge Drinking (BD) corresponds to episodes of ingestion of large amounts of ethanol in a short time, typically <= 2 h. BD occurs across all populations, but young and sports-related people are especially vulnerable. However, the short- and long-term effects of episodic BD on skeletal muscle function have been poorly explored. Young rats were randomized into two groups: control and episodic Binge-Like ethanol protocol (BEP) (ethanol 3 g/kg IP, 4 episodes of 2-days ON-2-days OFF paradigm). Muscle function was evaluated two weeks after the last BEP episode. We found that rats exposed to BEP presented decreased muscle strength and increased fatigability, compared with control animals. Furthermore, we observed that skeletal muscle from rats exposed to BEP presented muscle atrophy, evidenced by reduced fiber size and increased expression of atrophic genes. We also observed that BEP induced fibrotic and inflammation markers, accompanied by mislocalization of nNOS mu and high levels of protein nitration. Our findings suggest that episodic binge-like ethanol exposure alters contractile capacity and increases fatigue by mechanisms involving atrophy, fibrosis, and inflammation, which remain for at least two weeks after ethanol clearance. These pathological features are common to several neuromuscular diseases and might affect muscle performance and health in the long term.
Keywords: binge-drinking; alcohol; ethanol; skeletal muscle; muscle fatigue; fibrosis; atrophy; ccn2; ctgf; alcoholic myopathy